Al-Ghororu Wa Atsaruhu Fi Tijaroh Al-Ma'kulah Al-Mu'asharoh - Suratno Suratno (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2021)
This research is motivated by the curiosity of the ghoror influence on several forms ofmodern culinary business because since the end of 2019 several restaurants have gone viral for selling their food menus with the